Investigating the personal English learning environment of students with Down Syndrome: a preliminary analysis - Lara, Sara Veloso [UNESP]; Costa, Maria da Piedade Resende da (Univ Federal Santa Maria, 2023)
Teaching a foreign language to people without any intellectual disabilities is already complex, to people with special cognitive needs, such as Down Syndrome (DS), becomes even more complex, demanding from teachers technical skills and sensitivity to perceive the Personal Learning Environment of their students, which consists of teaching based on their individual interests and needs, in addition to contributing to the students' protagonism in acquiring their own knowledge. In this spectrum, TDICs play an important role on students' learning, since they are present in their daily lives, fostering the autonomy of students in the creation and selection of content and on their creativity. This article (in the process of a broader research), aimed to investigate the Personal English Learning Environment of two students with DS, based on the theory of Personal Learning Environment focused on the use of TDICs. It consisted of an action research. Two semi-structured interviews were conducted with students with DS and with those responsible for them, and analyzed based on Burns' Interpretive Paradigm (1999). The results indicate that the Personal Learning Environment of the language of these participants is limited, due to the rare contact with the language and TDICs. It can be concluded the necessity that researcher contributes for the participants to expand their own Personal Learning Environment of the English language, seeking strategies for this aim.
Keywords: Down Syndrome; English; Personal Learning Environment